THE LEGALITY OF ONLINE TRANSACTIONS IN MOSQUES AN ISLAMIC LAW PERSPECTIVE BASED ON AL-JAZIRI'S AL-FIQH 'ALA AL-MAZAH IB AL-ARBA'AH - Muhd Syahrul Akbar (Profit: Jurnal Kajian Ekonomi dan Perbankan Syariah)
ABSTRAK: